Trabeculectomy - A Review and 2 Year Follow Up - Jaais, F. (2004)
This study reviewed the trabeculectomies (TEs) carried out in University Malaya Medical Center between 1994 to 1998. One hundred and nine of 132 eyes operated were in the primary glaucoma group of which 63 (47.7%.) were of the open angle type and 46 (34.8%) were of the angle closure type. Twenty-three eyes belong to the secondary glaucoma group. Sixty-five eyes had plain or non-augmented trabeculectomy (TE) while 20 were augmented with mitomycin C (MMC) and 11 with 5 flourouracil (5FU). In 31 eyes the plain TEs were combined with extracapsular cataract extraction (ECCE) and 4 with phacoemusification. One case had combined ECCE and augmented trabeculectomy with mitomycin-C. The patients were followed up at I month, 6 months, 1 year and 2 years. Ninety-four of 132 (71.2%) eyes had successful surgery with intraocular pressure (IOP) of less than 21mmHg (tonometric success) at the end of 2 years. Four of these patients needed topical medication for the IOP control. More failures were seen in patients with cystic blebs than those with diffuse blebs. Complications include hypotony, shallow anterior chamber, cataracts and hyphaema. The majority of cases (53%) had no complications.